An anomalous late season change in the regional sea ice regime in the vicinity of the Mertz Glacier polynya, East Antarctica - Robert Massom; Jacka, K; Pook, MJ; Fowler, C; Adams, ND; Nathaniel Bindoff (2003)
No description available